Sequential-Constant Current Coulometric Determination of Sulfite-Thiosulfate and/or Sulfite-Ascorbic Acid in a Solution - PARHAM, H.; ZARGAR, B.; ALIZADEH, M. (Asian Journal of Chemistry, 2010)
A coulometric titration method is introduced for sequential determination of sulfite, thiosulfate and ascorbic acid in sulfite-thiosulfate or sulfite-ascorbic acid couple in a solution. Formaldehyde or acetaldehyde can be used to mask the sulfite component. Two sequential measurements of coulometric time, one for the both components in the mixture and one for the sample solution in which sulfite is masked by formaldehyde can be used to determine the concentrations of sulfite-thiosulfate and/or sulfite-ascorbic acid couples. Relative standard deviations (RSD) of all measurements lie in the range of 0.1-4 % . The effect of different parameters such as pH, concentration of reagents, ionic strength and effect of interferences are studied. The proposed method can determine 5.0 × 10-4–1.0 × 10-6 mol of thiosulfate and also 6.0 × 10-5 - 5.0 × 10-7 mol of ascorbic acid in a sample solution in the presence of 1.3 × 10-5–4.4 × 10-7 mol of sulfite. The current efficiency of the method is estimated to be ≥ 98.0 %. The proposed method can be used for the determination of sulfite-thiosulphate or sulfite-ascorbic acid in the presence of real sample matrixes (e.g., mineral waters and vitamin C tablets) with good accuracy and precision.